Trends in Israeli clinical trials registration "MyTrial" - Anat Engel; Ornit Cohen (BMC, 2024)
Abstract Background Clinical trial registration is critical for research transparency and integrity. Since 2005, the Declaration of Helsinki has required prospective registration of trials before subject recruitment. In Israel, the MyTrial registry was established in 2015 to register interventional trials and became mandatory in 2016 for ethical approval. The study aimed to analyze the registration practices, challenges, and trends in clinical trial registration in Israel using the local registry "MyTrial". Methods A total of 3,895 clinical trial records from 2011 to December 2022 were retrieved from the MyTrial platform and subjected to descriptive analysis. Results A significant increase occurred from 2016 to 2021 due to mandated registration, with a peak in 2020 (733 trials) and a decrease in 2022 (462 trials), likely due to COVID-19. Most of the trials included drugs (56%) or medical devices (33%). Geographically, 53% were from central Israel. Only 39% of the patients were registered at both MyTrial and ClinicalTrials.gov. 65% had no blinding. 47% featured unregistered products. 56% had not started recruitment. Since 2016, the number of advanced therapy trials has steadily increased, reaching 19 in 2022. There are gaps between registered trials and official government reports. Conclusion These findings provide valuable insights into the current landscape of clinical trial registration in Israel and highlight the need for improvements in compliance with prospective registration and adherence to the WHO-ICTRP standards.